Penerapan Metode Algoritma C4.5 dalam Penilaian Kelayakan Pemberian Kredit Kepada Mitra Usaha PT Arita Prima Sukses - Tukino Tukino (LPPM Universitas Putera Batam, 2023)
This research aims to investigate the application of the C4.5 algorithm method in assessing the feasibility of granting credit to business partners by PT Arita Prima Sukses. PT Arita Prima Sukses is a financial industry company with various business partners in need of financial support for their growth. The decision-making process regarding the provision of credit to business partners is a critical aspect of the company's risk management. The C4.5 method is one of the artificial intelligence methods used for decision-making based on rules identified from historical data. This research collects and analyzes historical data on credit approval for business partners by PT Arita Prima Sukses. The C4.5 method is then implemented to generate a predictive model that can assist in assessing the feasibility of future credit approvals. The results of the research indicate that the C4.5 method can significantly contribute to improving the accuracy of assessing the feasibility of granting credit to business partners. With this model, the company can be more effective in identifying potential risks and optimizing their credit portfolio. The implications of this research include enhancements in risk management and the potential for increased company profitability.